Trends and Destinations of Foreign Labour Migration in Nepal - Acharya, Chandra Prakash (Journal of Educational Research and Innovation, 2024)
Migration plays a crucial role in the interplay between population dynamics and development, particularly in the context of Nepal. This study aims to identify the trends and destinations of foreign labor migration from Nepal, highlighting its significance to the nation's economy. While recent data indicates a continuous increase in foreign employment patterns, there remains considerable uncertainty regarding the sustainability of these trends and their future levels. The study concluded that Nepal’s rising emigration, particularly to Gulf States and Malaysia, has significantly reshaped its economy, transitioning from agriculture to remittance dependency, with remittances now contributing the third-largest share of GDP globally. Despite this, slow implementation of the 2012 Foreign Employment Policy has prompted the Ministry of Labour and Employment to devise a five-year strategic action plan focusing on decentralizing migration management, improving remittance systems through innovative technologies, and ensuring social security for vulnerable groups. Additionally, addressing labor shortages post the 2015 earthquake and offering competitive wages to reduce labor outflow are critical. The study highlights the overlooked links between migration and development, emphasizing the need to optimize remittance utilization, human capital, and social capital to drive Nepal’s economic and social progress.